2012
DOI: 10.4103/0972-124x.100921
|View full text |Cite
|
Sign up to set email alerts
|

A comparative clinical evaluation of acellular dermal matrix allograft and sub-epithelial connective tissue graft for the treatment of multiple gingival recessions

Abstract: Background:Obtaining predictable and aesthetic root coverage has become an important part of periodontal therapy. Several techniques have been developed to obtain these results with variable outcomes. The aim of this study was to compare and evaluate the effectiveness of acellular dermal matrix allograft (ADMA) and subepithelial connective tissue graft (SCTG) in combination with coronally positioned flap in the treatment of multiple gingival recessions in aesthetic areas.Materials and Methods:Total 10 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…ARC was 95.77 ± 0.11% for the control group and 94.21 ± 0.20% for the test group. These observations are in accordance with other papers comparing the use of ADMA and CTG in cases of both individual and multiple gingival recession coverage using different operating techniques [27][28][29]. On the other hand, they contradict other studies which showed statistically better results when a connective tissue graft was applied [11,30].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…ARC was 95.77 ± 0.11% for the control group and 94.21 ± 0.20% for the test group. These observations are in accordance with other papers comparing the use of ADMA and CTG in cases of both individual and multiple gingival recession coverage using different operating techniques [27][28][29]. On the other hand, they contradict other studies which showed statistically better results when a connective tissue graft was applied [11,30].…”
Section: Discussionsupporting
confidence: 91%
“…Rahmani et al [30] observed mean root coverage of 70% for SCTG and 70% for the ADMA group. Similarly, Koudale et al [27] did not observe any statistically significant differences 6 months after multiple gingival recession coverage procedures using CPF with ADMA and CTG. In this case, the mean percent root coverage achieved was 94% and 97%, respectively.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Cairo et al confirmed this and showed that the treatment results of the MCAF alone vs. MCAF plus SCTG procedures were similar at sites with thick gingiva (>0.8 mm) but the SCTG improved results at sites with thin tissue [14]. In two studies, acellular dermal matrix allograft (ADM, AlloDerm®, BioHorizons) reduced gingival recession by at least 90% and showed no statistically significant difference from SCTG groups [15,27]. The efficacy of enamel matrix derivative (EMD, Emdogain®, Straumann) was compared to that of SCTG in two studies.…”
Section: Root Coverage Procedures and Predictability Subepithelial Comentioning
confidence: 72%
“…Studies using subepithelial connective tissue graft (SCTG) on multiple Miller Class I and II gingival recession defects show mean percent root coverage ranging from 77 to 98%, with only 4 out of 17 studies reporting less than 90% [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Other than coronally positioned flaps, flap designs used include tunnel technique [12,13], modified coronally advanced tunnel (MCAT) technique [26], modified coronally advanced flap (MCAF) technique by Zucchelli and De Sanctis [17,29], and a modified coronally positioned flap with a horizontal incision in the alveolar mucosa [20].…”
Section: Root Coverage Procedures and Predictability Subepithelial Comentioning
confidence: 99%